Internet of energy handbook - Kumar, Pawan 1977-; Nikolovski, Srete; Dong, Z. Y. (CRC Press, 2021)
"The Internet of Energy (IoE), with the integration of advanced information and communication technologies (ICT), has led to a transformation of traditional networks to smart systems. This handbook of research on Internet of Energy provides updated knowledge in the field of energy management with an Internet of Things (IoT) perspective. It explains the technological developments for energy management leading to reduction in energy consumption through topics like smart energy systems, smart sensors, communication, techniques and utilization. Dedicated sections cover varied aspects related to renewable sources of energy, power distribution and generation and so forth"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Electric power systems -- Automatic control; Electric power distribution -- Data processing; Energy conservation -- Data processing; Internet -- Industrial applications; Réseaux électriques (Énergie); Commande automatique; Économies d'énergie; Informatique; Internet; Applications industrielles; COMPUTERS / Networking / General; SCIENCE / Energy; TECHNOLOGY / Electricity; Electric power distribution; Data processing; Electric power systems; Automatic control; Energy conservation; Data processing; Internet; Industrial applications